Evaluation of Attitudes of Students Studying at State and Private Universities towards Distance Education - Kaan Kaya; Erdem Subak; Ceren Agaoglu; Yunus Sadır; Abdorreza Eghbal Moghanlou (Journal of Educational Issues, 2024)
With compulsory distance education in Turkey during the pandemic, the positive and negative effects of distance education have been investigated. In this study, the views of 256 students (162 males, 94 females) with a mean age of 21.5±3.457, studying in various departments in the primary field of sports sciences at state (n = 95) and foundation (n = 161) universities, on distance education and face-to-face education. It was taken with the Attitudes towards Distance Education Scale and compared statistically. In addition to frequency and distribution analysis, an Independent Sample T-Test was applied for statistical analysis, and the confidence interval was determined as 95% (p < 0.05). As a result of the research, it was seen that the students found face-to-face education more effective. It was noted that students who found face-to-face teaching more effective than other students agreed with the view that distance education is not engaging with a significant difference (p < 0.05). The same students also stated that they disagreed with the opinions that qualified results can be obtained from distance education applications. According to students ‘ opinions, this study provides educators with information about some of the missing points of distance education compared to face-to-face teaching. The minus points of distance education can be detailed with surveys to be made with more participants.